2015
DOI: 10.1016/j.cjca.2015.07.727
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Pcsk9 Inhibitor Evolocumab in Patients With Mixed Hyperlipidemia

Abstract: Purpose Evolocumab significantly reduces low-density lipoprotein-cholesterol (LDL-C); we investigated its effects on LDL-C lowering in patients with mixed hyperlipidemia. Methods We compared the efficacy and safety of evolocumab in hypercholesterolemic patients selected from the phase 2 and 3 trials who had fasting triglyceride levels ≥1.7 mmol/L (150 mg/dL elevated triglycerides) and <1.7 mmol/L (without elevated triglycerides). Fasting triglyceride level ≥ 4.5 mmol/ L at screening was an exclusion criterion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The reductions of LDLC, non-HDLC, and apoB obtained with anti-PCSK9 therapy are similar in patients with and without mixed hyperlipidemia, reflecting higher circulating concentrations of TG and remnant-like lipoproteins. Efficacy analysis of 3146 participants in 4 studies of evolocumab showed that the mean percentage change from baseline for patients with or without increased fasting TG Ͼ150 mg/dL (1.7 mmol/L) followed a similar pattern for LDLC (Ϫ67% and Ϫ65% vs placebo), non-HDLC (Ϫ53% and Ϫ54%), and apoB (Ϫ49% and Ϫ50%) (133 ). A similarly high proportion of evolocumab-treated NCEP III high-risk patients with and without increased TG achieved the LDLC target of Ͻ70 mg/dL (1.8 mmol/L) (82% vs 81%, respectively) and Ͻ100 mg/dL (2.6 mmol/L) (92% vs 92%, respectively).…”
Section: On-treatment Discordancesmentioning
confidence: 98%
“…The reductions of LDLC, non-HDLC, and apoB obtained with anti-PCSK9 therapy are similar in patients with and without mixed hyperlipidemia, reflecting higher circulating concentrations of TG and remnant-like lipoproteins. Efficacy analysis of 3146 participants in 4 studies of evolocumab showed that the mean percentage change from baseline for patients with or without increased fasting TG Ͼ150 mg/dL (1.7 mmol/L) followed a similar pattern for LDLC (Ϫ67% and Ϫ65% vs placebo), non-HDLC (Ϫ53% and Ϫ54%), and apoB (Ϫ49% and Ϫ50%) (133 ). A similarly high proportion of evolocumab-treated NCEP III high-risk patients with and without increased TG achieved the LDLC target of Ͻ70 mg/dL (1.8 mmol/L) (82% vs 81%, respectively) and Ͻ100 mg/dL (2.6 mmol/L) (92% vs 92%, respectively).…”
Section: On-treatment Discordancesmentioning
confidence: 98%
“…The reduction of PCSK9 with the PCSK9 inhibitors is associated with mild/moderate reductions of TRG levels (Table 1). 26 31 For example, in the recently published FOURIER trial, evolocumab significantly reduced serum TRG levels compared with placebo (−16.7% vs −0.7%, P < .001). 3 Several mechanisms affecting both secretion and catabolism of TRG-rich lipoproteins can explain the PCSK9 inhibitors-mediated reduction of TRGs.…”
Section: Effects Of Pcsk9 Inhibitors On Serum Trg Concentrationmentioning
confidence: 99%
“…This is consistent with the notion that risk of ASCVD is more directly related to the number of apoB-containing particles (reflected by apoB measurement) than to the cholesterol content of lipoproteins [10]. The implication of discordant LDLC vs. apoB (one normal, the other high) is most evident in patients with predominant small, cholesterol-depleted LDL particles who present with "optimal" concentrations of TC and LDLC -a profile that is especially prevalent among individuals with the metabolic syndrome or diabetes and in those taking medications, such as statins and anti-PCSK9, that reduce LDLC to a greater extent than apoB [87][88][89]. This necessarily results in on-treatment LDL and VLDL particle numbers that are higher than would be anticipated from the concurrent LDLC follow-up measurement and may explain part of residual risk among statin-treated patients [62,90].…”
Section: Apolipoprotein Bmentioning
confidence: 99%